Uji Aktivitas Antidiabetes Ekstrak Etanol Daun Pala (Myiristica Fragrans) Terhadap Tikus(Rattus Norvegicust) Galur Wistar Jantan Yang Diinduksi Aloksan - Aulia Debby Pelu; Pia Batmomolin; Salama Nurlette (Jurnal Kesehatan Amanah, 2021)
Nutmeg is known as a spice plant that has economic value and multipurpose because every part of the plant can be used in various industries. Compounds contained in nutmeg leaves include alkaloids, triterpenoids, tannins and 2 flavonoids. The purpose of this study was to determine the antidiabetic effect of ethanolic extract of nutmeg leaf (myristica frangrans) against male wistar white rats (Rattusnorvegicus) induced by alloxan administered intraperitoneally and compare its effectiveness with glibenclamide. This study used five treatment groups, namely the administration of aquadest as a negative control, glibenclamide as a positive control and ethanol extract of nutmeg leaves at a dose of 100 mg/kg BW, 200 mg/kg BW and 300 mg/kg BW as control treatments. Blood glucose measurements were carried out on day 0 (three days after induction), day 3, day 7 and day 10. The results showed that the ethanol extract of nutmeg leaf (myristica frangrans) TEST ACTIVITY can reduce blood glucose levels. At a dose of 300 mg/kg but not exceeding the decrease in blood sugar in the administration of glibenclamide. Giving ethanol extract of nutmeg leaves (myristica frangrans) also has activity to repair damage to pancreatic -cells in white rats (Rattus norvegicus) induced by alloxan.